Suitability of viability assays for testing biological effects of coated superparamagnetic nanoparticles - Baehring, Franziska; Schlenk, Florian; Wotschadlo, Jana; Buske, Norbert; Liebert, Tim; Bergemann, Christian; Heinze, Thomas; Hochhaus, Andreas; Fischer, Dagmar; Clement, Joachim H. (IEEE Transactions on Magnetics, 2013)
The aim of this study was to establish an in vitro model test system for the analysis of cellular effects of nanoparticles on endothelial cells using the human brain microvascular endothelial cell line HBMEC, a representative of the blood-brain barrier. At first we defined a toxic end point by using superparamagnetic iron oxide nanoparticles coated with cationic substances (polyethylenimine, chitosan, diethylamine ethyl). To study the toxic effects of nanoparticles we evaluated three different viability assays and one cytotoxicity assay for their suitability. We could show that a luminescence-based assay is most promising for an accurate testing, because it is reproducible and unaffected by assay conditions and reagents. © 1965-2012 IEEE.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Iron oxide; superparamagnetic nanoparticle; viability assay